Ramadan and Eid - "Khan, Saniyasnain" (China; Goodword Book, 2024)
Ramadan and Eid gently introduces young children to the blessed month. Through simple and engaging text, it helps youngsters understand the special meaning of Ramadan in a way they can relate to. Beautiful illustrations bring the stories and lessons to life, capturing their attention and imagination. The book highlights important values from the Quran, such as patience, tolerance, kindness, and thankfulness. These concepts are presented in a warm and accessible way that encourages reflection and learning. Children will enjoy discovering the traditions and celebrations of Ramadan and Eid. It$1 (Bs a perfect tool to nurture their spiritual growth during this special time. The gentle messages inspire good character and empathy. This book makes learning about faith joyful and memorable for little hearts. Share the blessings of Ramadan with a story that touches both mind and soul. Best suited for children under 5years of age.s
Keywords: Islamic values